The greatest polar expedition of all time : the Arctic mission to the epicenter of climate change - Rex, Markus; Göring, Marlene (Greystone Books, 2022)
"A captain's tell-all about the world's largest Arctic expedition--an illuminating account of seafaring adventure, Arctic natural history, and cutting-edge climate science. The book about the Mosaic Expedition: as seen in the documentary film Arctic Drift, Atmospheric scientist Markus Rex recounts the monumental Arctic expedition he captained for one year in this gripping and authoritative book. A groundbreaking step towards understanding the climate crisis, the MOSAiC expedition--launched in 2019 by the Alfred Wegener Institute for Polar and Marine Research--was the first of its kind, journeying deep into the epicentre of climate change, the Arctic, to seek hard-to-find and potentially world-changing scientific data. Rex begins with life aboard the Polarstern, a powerful icebreaker ship that is frozen into fragile ice and carried across the Arctic by the Transpolar Drift. Away from the rest of the world, the team prepares for life under brutal conditions, constructing "cities" and "towns" on the ice where they will study the Arctic ecosystem, its atmosphere, ocean, sea ice, and more. A terrifying feat that had never been attempted before, the team of hundreds of scientists perform their research during terrifying storms, cracking ice floes, frost-bite, and even quarantines as Covid-19 sweeps the globe. But there are heartwarming moments, too, as Markus Rex describes Christmas parties on the ice and polar bears playing with scientific equipment like puppies. He muses on expeditions past, such as the ill-fated Franklin Expedition, and Fridtjof Nansen's Fram expedition, which he follows as a guide. And he explores answers to the pressing questions facing the Arctic today: How will climate change impact this precious ecosystem--and therefore the rest of the world? What is the best way to protect the Arctic? Interweaving history, science, and memoir, The Greatest Polar Expedition of All Time is a page-turner about the teamwork it takes to complete a risky goal, all in the name of understanding--and responding to--the climate crisis."--